Analysis of English Teacher’s Differentiated Assessment Strategy in ELT Classroom at SMP Negeri 1 Negara - Yasa, I Gede Ardana; Wahyuni, Luh Gede Eka; Paramartha , A.A. Gede Yudha (Indonesian Research Journal on Education, 2025)
The aim of this research is to explain various differentiated assessment strategies and the challenges faced by English teachers at SMP Negeri 1 Negara during the teaching and learning process in the classroom. The research was conducted using a qualitative descriptive approach. The subjects of this research were three English teachers at SMP Negeri 1 Negara. Data for this research was collected through classroom observations and interviews with three English teachers at SMP Negeri 1 Negara, with researchers using observation sheets and unstructured interviews. Data analysis for this research was carried out by analyzing the results of classroom observations and conducting interviews with English teachers about the differentiated assessment strategies used in teaching English and the challenges that English teachers face when implementing differentiated assessment strategies in the classroom. This research found that English teachers at SMP Negeri 1 Negara used a variety of differentiated assessment strategies to teach English, including quiz, assignments, task-based assessment, discussions, and speaking-performance. However, other assessment strategies have not been implemented in differentiated context. Furthermore, this research shows that the challenges faced by English teachers include limited time in preparing various differentiated assessments, teachers' continuous struggle to teach in large classes, and the diversity of students' learning needs and abilities.